Ex vivo quantification of lanthanum and gadolinium in post-mortem human tibiae with estimated barium and iodine concentrations using K x-ray fluorescence. (3rd September 2019) - Nguyen, Joanna; Crawford, Daniel; Howarth, David; Sukhu, Balram; Pejović-Milić, Ana; Gräfe, James L
Abstract: Objectives : Lanthanum (La) and gadolinium (Gd) are known to deposit in bone of exposed populations, namely those who are orally administered lanthanum carbonate (LaC, La2 (CO3 )3 ) or are injected with Gd-based contrast agents, respectively. In this work, bone La and Gd concentrations from the environment and diet were measured using x-ray fluorescence in ten post-mortem human tibiae. As a secondary objective, bone barium (Ba) and iodine concentrations were estimated. Approach : Two calibration lines were produced for La and Gd and the minimum detection limits (MDLs) of the system were determined using a 180° irradiation-detection geometry. Main results : The MDLs of the system were 0.4 µ g La g −1 bone mineral and 0.5 µ g Gd g −1 bone mineral. The mean concentrations were −0.02 ± 0.1 µ g La g −1 bone mineral and 0.1 ± 0.2 µ g Gd g −1 bone mineral in tibiae. The average Ba and iodine concentrations estimated from the experimental La calibration line and Monte-Carlo derived sensitivity factors were determined to be 3.4 ± 0.8 µ g Ba g −1 bone mineral and −0.5 ± 0.3 µ g iodine g −1 bone mineral. Since it was discovered that four donors previously received an iodine-based contrast agent, the mean concentrations in these donors was 27.8 ± 28.4 µ g iodine g −1 bone mineral. Significance : The XRF system has determined baseline concentrations of these four heavy metals in trace quantities from natural exposure pathways (with the exception of iodine in four donors). This indicates that the system can measure low levels in ex vivo tibiae samples and can potentially be further developed for in vivo studies involving live subjects who are directly exposed to these metals.